Associations between urinary iodine concentration and the prevalence of metabolic disorders: a cross-sectional study - Shen, Xia; Yang, Long; Liu, Yuan-Yuan; Zhang, Xue-He; Cai, Ping; Huang, Jian-Feng; Jiang, Lei (Frontiers in Endocrinology, 2023)
BACKGROUND: Fewer studies on the role of iodine in extrathyroidal function. Recent research has shown an association between iodine and metabolic syndromes (MetS) in Chinese and Korean populations, but the link in the US population remains unknown. PURPOSE: This study aimed to examine the relationship between iodine status and metabolic disorders, including components associated with metabolic syndrome, hypertension, hyperglycemia, central obesity, triglyceride abnormalities, and low HDL. METHODS: The study included 21,546 adults aged ≥ 18 years from the US National Health and Nutrition Examination Survey (2007-2018). Participants were divided into four groups based on their iodine nutritional status, as recommended by the World Health Organization: insufficient (UIC < 100 g/L), normal (100 g/L ≤ UIC＜ 300 g/L), high (300 g/L ≤ UIC ＜400 g/L), and very high (≥ 400 g/L). The Odds ratio (OR) for MetS basing the UIC group was estimated using logistic regression models for our overall population and subgroups. RESULTS: Iodine status was positively associated with the prevalence of MetS in US adults. The risk of MetS was significantly higher in those with high UIC than in those with normal UIC [OR: 1.25; 95% confidence intervals (CI),1.013-1.546; p = 0.038). The risk of MetS was lower in the low UIC group (OR,0.82; 95% CI: 0.710-0.954; p = 0.010). There was a significant nonlinear trend between UIC and the risk of MetS, diabetes, and obesity in overall participants. Participants with high UIC had significantly increased TG elevation (OR, 1.28; 95% CI: 1.002-1.528; P = 0.048) and participants with very high UIC had significantly increased risk of diabetes (OR, 0.68; 95% CI: 0.538-0.849, p = 0.001). Moreover, subgroup analysis revealed an interaction between UIC and MetS in participants aged < 60 years and ≥ 60 years, and no association between UIC and MetS in older participants aged ≥ 60 years. CONCLUSION: Our study validated the relationship between UIC and MetS and their components in US adults. This association may provide further dietary control strategies for the management of patients with metabolic disorders.